Multimetallic catalysed radical oxidative C(sp3)–H/C(sp)–H cross-coupling between unactivated alkanes and terminal alkynes - Shan Tang (Nature Portfolio, 2016)
Cross coupling via the activation of two carbon-hydrogen bonds avoids the need for organometallic coupling partners and associated waste. Here, the authors report a radical process that allows selective coupling between alkynes and non-activated C(sp3)-H groups via a multimetallic catalytic system.